Beyond `crude pragmatism` in sports coaching: Insights from C.S. Peirce, William James and John Dewey: A Commentary - Campos, D. G. (International Journal of Sports Science & Coaching, 2017)
Introduction: A central aim of Simon Jenkins's article is to provide coaching theorists-practitioners with a clearer understanding of philosophical pragmatism as a viable approach to coaching—an approach that is both intellectually well funded and effective for achieving desired goals. By clarifying, Jenkins also seeks to recommend this way of coaching. For him, philosophical pragmatism would lead to better coaching than "crude pragmatism" because it is not merely practicalist—that is, focused on short-term results through ad hoc fashionable coaching techniques (techne). It is rather a method, facilitated by a distinctive temperament and guided by practical wisdom (phronesis), that emphasizes goal-directed experimentation, observation of results, individual and communal reflection upon those results, and consequent revision of the assumptions, habits, goals, and purposes that leads to renewed experimentation. I think Jenkins has described successfully various elements of a well-developed pragmatist coaching practice. His conclusions, though, are brief. As a complement to his article, then, I want to offer my own descriptive summary of a pragmatist coaching practice from the specific standpoint of Peircean philosophy. I will try to articulate my general Peircean viewpoint in a clear and succinct way. FROM AUTHOR